(untitled) (Journal of Oriental Studies, 2021)
The purpose of this article is to study and evaluate the experience of the Al-Farabi Kazakh National University in training personnel for the system of international relations, which became an extremely urgent task during the period of strengthening the independence of Kazakhstan. At a time when the number of pressing global problems that cannot be solved by the forces of one nation, including such problems and threats as climate change, epidemics, food and water security, has increased significantly, the development of new diplomacy and new approaches is becoming inevitable. Knowledge diplomacy is based on the strategies of cooperation and interaction, which in recent decades have characterized the international activities of KazNU. al-Farabi. Only those who have deep and broad knowledge and tools of critical thinking and action that allow them to maintain a clear mind and balanced decisions can predict, give advice and develop a strategy for expected events in the outside world and unexpected shocks for the world community. Since the Kazakh National University is responsible for the training of international specialists, the teachers of the Faculty of Oriental Studies develop the awareness and competence of graduates in relation to international and regional problems in the countries of the East, the most relevant for Kazakhstan, use real practical examples in the field of public policy, world politics, as well as international security and economy. Key words: higher education, diplomatic ties, graduates, science, cooperation.